Transactional sexual relationships as obstacles to the full enjoyment of sexual and reproductive health and rights of adolescent girls in South Africa - Killander, Magnus (University of Pretoria, 2023)
Mini Dissertation (LLM (Socioeconomic Rights))--University of Pretoria, 2022.